Experimental investigation to determine necking of commercially pure titanium sheets using a time-of-flight camera and Heaviside-digital image correlation. (May 2023) - Jedidi, Mohamed Yessine; Valle, Valéry
Highlights: A new process based on the nakazima test is employed to better determine the ductility limit of CP-Ti thin sheets. The advantage of using the ToF camera on the determination of necking limit is investigated. The application of the DIC and the H-DIC techniques to determine ductility limits of CPTi sheet metals is highlighted. The H-DIC parameters is very sensitive to the occurrence of localized necking. Abstract: The plastic instability evolution in polycrystalline metallic materials is a key to understanding the deformation processes during mechanical loading. Plasticity assessments of commercially pure titanium (CP-Ti) can be performed to enhance its mechanical properties. The aim of the present investigation is to determine the plastic deformation during the metal forming processes of CP-Ti sheets at room temperature. This localized deformation might affect the ductility of the sheets' materials during the forming processes due to their complex strain paths. Therefore, this study is focused on the determination of Forming Limit Diagrams (FLDs) of CP-Ti sheets in different strain paths based on experimental Nakazima test. The latter is employed to determine the complete FLD using several specimens with various geometries to achieve different strain paths in tensile tests. For this purpose, the strain field measurements before cracking are carried out by the Digital Image Correlation (DIC) procedure. The detection of macroscopic cracks is determined by the Heaviside-DIC (H-DIC). During experimental tests, several images are taken with an integrated camera. The captured images are analyzed by DIC and H-DIC. In this work, a second depth camera is accurately calibrated. Thus, depth and standard cameras address most error sources inherent in the time-of-flight (ToF) technology within a unified calibration framework. Therefore, the automatic calibration method of the consumer ToF camera is used and developed for the first time with H-DIC technique, in the framework of material formability, to better determine the ductility limit of CP-Ti.